Dirt under our fingernails: Daylighting waste at the Dome - Budgett, Jeanette (Interstices: Journal of Architecture and Related Arts, 2022)
Auckland City’s burgeoning waste stream is projected to exceed current landfill capacity by 2026. A proposed new landfill site in the forested Dome Valley, 70 miles north of Auckland, is controversial. In the secluded valley, a capped landfill will hide the inconvenient and relegated externalities of modern consumer society. Since the second half of the twentieth century, such practices have come under increasing censure around the world, particularly from environmentalists and indigenous people. Contemporary city infrastructure has prioritised making waste flows invisible. Against this emphasis, this paper considers conceptual artistic practice from the 1970s that made visible the matter, politics, and potential of overlooked residue. The creative engagements of Billy Apple, Mierles Laderman Ukeles, and Noel Lane reframe waste residue and processes as materially and ethically continuous with the sites and societies from which they come. The paper re-reads these instances of artistic practice in terms of infrastructures of city waste disposal, suggesting ways in which art practice might help build new approaches to waste’s accumulation.